Wh- In Situ Production in Child French* - Gotowski, Megan (Linguistica Atlantica, 2018)
This article addresses claims that French children produce more wh-in situ questions than adults, and that this is motivated by a desire for more “economical” structure in regard to wh-question formation. Experimental results of an elicitation study with 19 children (3;09-5;08) conducted in Paris are reported. Results indicate that children do not demonstrate a preference for wh-in situ, contra previous research with corpora, and most are in fact completely adult-like. As a consequence, I argue that children are not motivated by an economical “in situ strategy”, and that they have the mechanism to produce fronted wh-questions with overt movement from as young as 3 years. Keywords: first language acquisition, syntax, wh-movement, wh-in situ, child French